Transformations of the poeticworried vision of poet Mahmoud Darwish Between 1964-1984 - Maya, Fakher; Boutros, Rita (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Mahmoud Darwish developed in his poetic style between 1964-1984, and he devised a language and his own style . As a matter of concern and uneasiness due to his situation in his occupied country, his poetry was a painting in which he combined poetry and prose. Combining mystery, clarity, difficulty and ease, his poetic language was fresh and full of beautiful pictures and rhythm . The innovative musician, who used the symbol to express his anxiety and pain, came up with an honest example of his condition . And has clearly called for a professional and humane function of poetry that makes his artistic beauty in the service of man, his experiences . And its big issues, and not only borders on the outer beauty, but beyond, and there is no doubt that the first literary culture . To Mahmoud Darwish derived from the literary Arab in which the poet lives in his homeland Palestine, and this is what made. His poetic vision is concerned and unstable.